Cost-effectiveness study of antidiabetic drugs in type 2 diabetes mellitus patients from Mumbai, India - Limaye, Dnyanesh; Todi, Krishna; Shroff, Jay; Ramaswamy, Ashutosh; Kulkarni, Priyanka; Limaye, Vaidehi; Fortwengel, Gerhard (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes is fast gaining the status of a potential epidemic in India, with >62 million individuals currently diagnosed with the disease. India currently faces an uncertain future in relation to the potential burden that diabetes may impose on the country. An estimated US$ 2.2 billion would be needed to sufficiently treat all cases of type 2 diabetes mellitus (T2DM) in India. Many interventions can reduce the burden of this disease. However, health care resources are limited; thus, interventions for diabetes treatment should be prioritized. The present study assesses the cost-effectiveness of antidiabetic drugs in patients with T2DM from Mumbai, India. Methods: A prospective cross-sectional study was performed to assess the cost-effectiveness of antidiabetic drugs in patients with T2DM. Face-to-face interviews were conducted by using a validated questionnaire in a total of 152 (76 males, 76 females) patients with T2DM from F-North Ward, Mumbai, India. Cost-effectiveness was determined on the basis of cost of antidiabetic drug/s, efficacy, adverse drug reactions, safety of administration, frequency of administration, and bioavailability. Results: For treatment of T2DM in non-obese participants, Glimepiride+Pioglitazone costed least (`3.7) per unit of effectiveness followed by Glimepiride (`6.6), Gliclazide (`8.1), Repaglinide (`24.5), and Vildagliptin (`45.2). For treatment of T2DM in obese participants, Metformin cost least (` 6.7) per unit of effectiveness followed by Glimepiride + Metformin (`5.9) and Repaglinide (`24.5). Conclusions: In case of non-obese participants, cost effectiveness and prescribed treatments did not show a match, while for obese participants prescribed treatments were in line with cost effectiveness.